2014
DOI: 10.1016/j.jtcvs.2013.08.062
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up period after transumbilical thoracic sympathectomy for hyperhidrosis: Outcomes and consequences

Abstract: Transumbilical thoracic sympathectomy is an efficacious alternative to the conventional approach. This technique avoided the chronic pain and chest wall paresthesia associated with the chest incision. In addition, this novel procedure afforded maximum cosmetic benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…In further support of the transumbilical approach, patients who had received this intervention reported significantly greater satisfaction with cosmetic outcome as well (94.1% vs 71.9%; P =0.036) 74. In a subsequent study by Zhu et al,75 a 1-year follow-up was provided for 35 patients who had received transumbilical thoracic sympathectomy for palmar and/or axillary HH. At 1 year, a 97.1% success rate (34 of 35) for palmar HH was noted, and a 72.2% success rate (13 of 18) was reported for axillary HH 75.…”
Section: Surgerymentioning
confidence: 98%
See 2 more Smart Citations
“…In further support of the transumbilical approach, patients who had received this intervention reported significantly greater satisfaction with cosmetic outcome as well (94.1% vs 71.9%; P =0.036) 74. In a subsequent study by Zhu et al,75 a 1-year follow-up was provided for 35 patients who had received transumbilical thoracic sympathectomy for palmar and/or axillary HH. At 1 year, a 97.1% success rate (34 of 35) for palmar HH was noted, and a 72.2% success rate (13 of 18) was reported for axillary HH 75.…”
Section: Surgerymentioning
confidence: 98%
“…Beyond the risk of CH following ETS, there is also concern about cosmetic outcome and risk of chronic chest wall pain and paresthesias 74,75. Although the thoracic wall approach with endoscopy involves the creation of relatively small incisions,75 the desire for a less invasive approach and interest in preventing intercostal nerve injury have driven new procedural innovations.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…CS is generally reported in 28-100% of cases during the early post-operation period, but 2 to 3 years after surgery its occurrence rate is reduced to 21%-47%. Although CS has a rather high prevalence, it is severe in only 0-14% of patients during the early postoperation period, and its severity declines with time (Table 1) [1,7,21,26,29,[33][34][35][36][37][38].…”
Section: Surgery Outcomes and Consequencesmentioning
confidence: 99%
“…No paper was found that compared the transumbilical approach with transthoracic thoracoscopic surgery [1,7,21,28,29].…”
Section: Complications Of Surgerymentioning
confidence: 99%